Impact of Workplace Bullying on Job Burnout - Zanabazar, Altanchimeg; Jigjiddorj, Sarantuya; Jambal, Tsolmon (SCAD Independent, 2023)
Workplace bullying can result in serious consequences for both employees and employers. Unfortunately, despite the guarantee of safe employment, workplace harassment, violations of employment rights, and bullying continue to occur within organizations. This study investigated the relationships and pathways between workplace bullying and job burnout in insurance company employees. The study consisted of 189 employees. The data were collected using a sociodemographic data questionnaire, the Negative Acts Questionnaire-Revised, and Maslach Burnout Inventory Scale. The model was tested using path analysis techniques within structural equation modeling. The analysis results demonstrated a strong positive correlation between workplace bullying and job burnout. The study revealed that assigning underperforming or impossible tasks, setting unachievable goals, and excessive workloads are indicators of workplace bullying. Hostile acts such as spreading rumors, speaking maliciously, ignoring someone intentionally, and teasing someone also contributed to diminished personal achievements and underperformance. Intimidation tactics, such as recalling mistakes or domineering behavior, also led to job burnout. The study's findings suggest that employers should be aware of workplace bullying's harmful effects and take measures to prevent it from occurring to protect their employees' well-being and organizational success.